Estimation of Global Solar Radiation using Modifed Angstrom Empirical formula on the basis of Meterological parameters in Himalaya Region Pokhara, Nepal - Poudyal, Khem N. (Journal of the Institute of Engineering, 2016)
This research work proposes the coefficient equation of modified Angstrom model using sunshine hour and meteorological parameters for the estimation of global solar radiation in Himalaya Region Pokhara (28.22° N, 83.32° E), Nepal . This site is about 800.0 m above from the sea level lying just 20.0 km south of the Machhaputre Himalayas. The model coefficients a and b obtained in this research are 0.43 and 0.23 respectively. The performance parameters of the model are: Root Mean Square Error RMSE = 0.13 MJ/m2 /day, Mean Bias Error MBE= 0.02 MJ/m /day Mean Percentage MPE= 5 percent and coefficient of determination R2 = 0.70. Journal of the Institute of Engineering, 2015, 11(1): 158-164